COUNTERACTNG THE BRIBERY OF JUDGES UNDER THE CRIMINAL LAW OF SOME OTHER COUNTRIES - Дідик, Сергій Євгенович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article analyzes the norms of criminal legislation of some foreign countries, which stipulate the responsibility of judges for bribery. On the basis of the study, it is concluded that the use of foreign experience is needed to improve the national criminal law in this area.